The constitutional framework for regulation of the position of the Roma community in the Republic of Slovenia - Zagorc, Saša (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
In the first part, author questions the need to regulate the matters regarding the Roma Community in the highest legal act, as it was done in the Constitution of the Republic of Slovenia. He believes that the introduction of the collective rights in the Constitution may result as inappropriate in thelong-term. The second part deals with normative analysis of the status of Roma in Slovenia, in which the constitutional framework for protection of the national communities mentioned in the Constitution is presented, and, finally,different constitutional status of the national communities (minorities) is elaborated. Such differentiation exposes the question whether the Romany community is entitled to have its own member of the National Assembly. By using all interpretation techniques it can be concluded that the Romany community at present does not enjoy the same level of positive discrimination as the two other national communities in Slovenia.
Keywords: etnične skupine; Romi; pravno varstvo; zakonodaja; ustavno varstvo; Slovenia; Slovenija